Nonlinear dynamic buckling of full-filled fluid sandwich FGM circular cylinder shells - Phu, Khuc Van; Doan, Le Xuan (Vietnam Journal of Mechanics, 2019)
This paper is concerned with the nonlinear dynamic buckling of sandwich functionally graded circular cylinder shells filled with fluid. Governing equations are derived using the classical shell theory and the geometrical nonlinearity in von Karman–Donnell sense is taken into account. Solutions of the problem are established by using Galerkin’s method and Runge–Kutta method. Effects of thermal environment, geometric parameters, volume fraction index k and fluid on dynamic critical loads of shells are investigated.